Efektivitas Tax Amnesty Terhadap Peningkatan Penerimaan Pajak Nasional dan Arah Kebijakan Pemerintah Pasca Tax Amnesty (Periode Pengamatan Tahun 2012-2017) - Wuku Astuti (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2018)
This study examines the effectiveness of Tax Amnesty on the increase of national tax revenue and the direction of government policy after Tax Amnesty (observation period 2012-2017). Population in this research is the ralization of the national tax revenue report and data realization of tax revenues from Sunset Policy. While the sample is focused on the report on the ralization of national tax revenue in 2012-2017 and data on tax revenue from Sunset Policy (2015) and Tax Amnesty (2016-2017). The normality test of data distribution is done by classical assumptiontest. To test the influence of independent variable to dependent variable done regression analysis. While testing the hypothesis is determined bay t-test. The test results show that Tax Amnesty is less effective in increasing tax revenue.